Az önkormányzati finanszírozás lehetséges jövőbeli irányai - Lados, Mihály (Tér és Társadalom, 1998)
The paper is making a picture of financial sources, helping Hungarian local governments improving fissal independence and on the other side, make secure the equalising system amongst settlements with different financial capacities. The first objective belongs to the governmental regulation system, the second has another outer connections too. These sources are using for moderating the differences on income-production through redistribution, or more effective expenditure system in governmental tasks. The other group of equipment use for improving income. production capacity belongs to regional policy. The social-economic transformation affected the regions in different ways in Hungary, resulting wider regional differences, than before. This situation came as a result of some dissimilar processes. The governmental infrastructure construction programs moderated the differences. At the same time the leader regions of transition – thanks for the activity of foreign investors – were the traditional more developed areas of the country (Budapest and its agglomeration zone, regional centres, Northwestern Transdanubia). A real equalising method means, that the local governments – laying in a peripheral area for example – has sources helping for local development. The basis of this method is stabilising sources of current functional expenditures. The desirable situation a certain resource-system, which help the local governments to widen free sources, or on the other hand improve the recent frittered system more effective, transparent and public. There are two ways in the Hungarian situation, to widen free sources for local governments. The first, change the divided personal income tax (PIT-) system as a local and a centralised part. The second way is developing the value-based property tax system. (In the last few years, we could see the strengthening role of local corporation tax, but in the author's opinion we must weaken the role of this taxation form in longer term, if we'd like a more effective local economy.) In the local taxation system, the most perspective class is the property-tax group and within this group we should develop the accommodation tax form, based on the value of flats. This change needs at least 4-5 years, similar the introducing of PIT- system in 1988. The nodal point of the process is preparing people for the changes. The moderating resources are present in the recent financial system, but extremely frittered, squandered way. The potential change should be the following: we should use only two moderating aiding forms of sources. The first, for helping on equalise the current functional expenditures, as a PIT-moderating support and the other for improving local development through an object-aid system. The source of these aids would come from the centralised part of PIT. It is necessary to upset, how to develop the normative-aid system, too. If we'd like to manage the normative form, together the resource regulation and moderating system, that would be enough to create a simple distribution form, based on 4-5 specimen. If we prefer the object-oriented financing system this form should be concentrated on only three areas (education, social-welfare, health), improving the role of private sector. Any other part – except financing ethnic minorities – would get out of the normative system. The pressure weight the source side down can reduce with a more rational service organising system. We can improve the more effective functioning in two ways. The first is decentralise functions, the other is stimulate associations of local governments for supplying common functions. This stimulating process based on financial regulation, rather than administrative way.